Avaliação da atividade antibacteriana, antiproliferativa e toxicológica in silico, in vitro, in vivo, ex vivo de um derivado da N-metil isatina - Dias, Gabriela Tafaela (2020)
The N-methyl-isatin derivative (ISACN) is a molecule obtained via the Morita-Baylis-Hillman Reaction (RMBH). In recent studies the activity against human leukemia cell lines HL-60 was found, making this molecule a promising drug candidate. This research aimed to investigate the antibacterial, antiproliferative effects, and to evaluate toxicity through in silico, in vitro, in vivo, ex vivo tests of a Morita-Baylis-Hillman (ISACN) adduct derived from N-methyl-isatin. Initially, the in silico approach was performed using software that is based on molecular descriptors. The antibacterial pharmacological activity test was performed by using a 96-well plate microdilution technique in vitro. The in vitro cell viability and proliferation assay was performed by the resazurin assay. Mutagenic potential was screened in vitro by the bacterial reverse mutation test (Ames test). In addition, in vivo methodologies were used to assess non-clinical toxicity through the acute toxicity test and in repeated doses based on OECD 423 and 407, respectively. Finally, levels of oxidative stress markers were analyzed in an ex vivo assay. In the in silico approach, ISACN presented good theoretical bioavailability after oral administration, good solubility, stability, absorption, and low theoretical toxicity. In the in vitro pharmacological tests ISACN showed unprecedented antibacterial activity, revealing good potential at minimum inhibitory concentrations (MIC) between 100 and 400 μg / mL, with 90% of bactericidal effect on gram-positive and gram-negative strains. It also showed low potential cytotoxic against HEK-293 non-tumor cells, and low or no antiproliferative activity against A375 and B16F10 melanoma strains. In the in vitro genotoxicity assay, low risk for ISACN can be attributed, as it did not demonstrate mutagenic potential in the S. typhimurium strains (Ames test). In the evaluation of acute non-clinical toxicity, ISACN presented low toxicity in vivo, according to the GSH classification. Changes in behavioral screening were absent, however, a reduction in dose-dependent food intake and a reduction in body weight gain were demonstrated. Also apparent, were changes in the serum calcium level and reduced platelet count. In repeated dose studies of ISACN, it was possible to observe greater sensitivity in male Swiss mice, who presented some mortality in the first days, higher rates of variation in behavioral, consumption, weight gain and biochemical parameters. Finally, in the analysis of the levels of the oxidative stress markers, ISACN induced an increase in lipid peroxidation at the highest concentration in females; however, results that did not induce oxidative stress were predominant. Given the above, it is concluded that ISACN has antibacterial activity with bactericidal effect, reduced cytotoxicity and antiproliferative activity against melanoma strains, good theoretical oral bioavailability, absence of genotoxicity, low acute toxicity and repeated dose toxicity, and does not induce oxidative stress. Therefore, it constitutes a promising molecule with potential pharmacological use.